Vegetarian and omnivorous nutrition - Comparing physical performance - Craddock, J. C.; Probst, Y. C.; Peoples, G. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Humans consuming vegetarian-based diets are observed to have reduced relative risk for many chronic diseases. Similarly, regular physical activity has also been shown to assist in preventing, and reducing the severity of these conditions. Many people, including athletes, acknowledge these findings and are adopting a vegetarianbased diet to improve their health status. Furthermore, athletes are incorporating this approach with the specific aim of optimizing physical performance. To examine the evidence for the relationship between consuming a predominately vegetarian-based diet and improved physical performance, a systematic literature review was performed using the SCOPUS database. No date parameters were set. The keywords vegetarian OR vegan AND sport OR athlete OR training OR performance OR endurance were used to identify relevant literature. Included studies (i) directly compared a vegetarian-based diet to an omnivorous/mixed diet, (ii) directly assessed physical performance, not biomarkers of physical performance, and (iii) did not use supplementation emulating a vegetarian diet. Reference lists were hand searched for additional studies. Seven randomized controlled trials and one cross-sectional study met the inclusion criteria. No distinguished differences between vegetarian-based diets and omnivorous mixed diets were identified when physical performance was compared. Consuming a predominately vegetarian-based diet did not improve nor hinder performance in athletes. However, with only 8 studies identified, with substantial variability among the studies` experimental designs, aims and outcomes, further research is warranted.